Pulse residual excited linear prediction - Shah, Asadullah; Shaikh, Muniba (IIUM Press, 2011)
Pulse Residual Excited Linear Prediction (PRELP) is a variant ofCELP encoding algorithm. The PREP, as its name suggests, instead of codebook, use pulses in codebook. This method reduces the searching time for a matching pulse from the codebook. In this chapter, PRELP algorithm is explained along with the design ofsuch codebook